PENGARUH BERBAGAI JENIS PUPUK ORGANIK TERHADAP PRODUKTIVITAS RUMPUT Panicum maximum, Setaria splendida, dan Pennisetum purpureum - Sahlan M; I W. Suarna; N.G.K. Roni (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2018)
Forage is the main feed that contains almost all the nutrients needed by ruminants. This study aimed to determine the productivity of Panicum maximum, Setaria splendida Stapf, and Pennisetum purpureum grass were given organic fertilizer and knew the best organic fertilizer for each type of grass. The study used a completely randomized design in split plot pattern. The first factor (main plot) consists of three types of grass; Panicum maximum, Setaria splendida, and Pennisetum purpureum. The second factor (sub plot / subplot) is a type of organic fertilizer; without fertilizer, manure, compost, and vermicompost. Each treatment was repeated three times so that it consisted of 36 experimental units. The results showed that the interaction between the treatment of the type of organic fertilizer with the type of grass occurred in the variable number of tillers and the dry weight of the stem. The types of compost in significant can increase the number of tillers, the number of leaves, the dry weight of the stems, the dry weight of the leaves, and the total dry weight of forage, compared to without fertilizer. The type of grass has a significant effect on all observed variables. Based on the results of the study it can be concluded that the interaction between the treatment of the type of organic fertilizer with the type of grass affects the number of tillers and the dry weight of the stem, the three types of grass have different productivity, while among the organic fertilizers provided, compost gives the best results. Keywords: grass, manure, compost, vermicompost